Republic of the Philippines - Improving Bureaucratic Performance : Assessment of the Performance-Based Bonus Scheme - World Bank (Washington, DC, 2015)
The objective of this policy note is to provide an empirically-based assessment of the Performance-based Bonus (PBB) initiative with the aim of providing recommendations on further improving the scheme, if necessary, for the remaining duration of the Aquino administration and beyond. The assessment is based on a large survey of government officials conducted by the World Bank from September 2013 to March 2014, in collaboration with the Department of Budget and Management and the Inter-Agency Task Force (IATF) on government performance. The note is structured as follows: the next section provides the fiscal context for the PBB, which is followed by a brief description of the survey methodology. The survey was not limited to the PBB but explored broader perceptions of pay levels as well as of other human resource management practices. This note however, focuses on the assessment of the PBB which is covered in the next section that details the main findings of the survey. The final section presents recommendations, and these recommendations are all for the immediate term given the limited time left for the Aquino administration.